Mengungkap Pengaruh Leverage, Likuiditas, dan Reputasi Underwriter terhadap Underpricing di Sektor Energy: Peran Ukuran Perusahaan sebagai Variabel Kontrol (2021-2023) - Terentia, Rachel Finna; Riswan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the effect of leverage, liquidity, and underwriter reputation on underpricing and the role of company size in controlling leverage, liquidity and underwriter reputation on underpricing. This study applies quantitative analysis using a sample of companies from the energy sector listed on the Indonesia Stock Exchange in the period 2021-2023, with a purposive sampling method for sample selection. The results of this study are that leverage and liquidity have a positive and significant effect on underpricing, underwriters have a negative and significant effect on underpricing and the role of company size weakens the relationship between leverage, liquidity, underwriters on underpricing.